LESS utopia: Architectural visions and future demands (student workshop) - Blum, Daniel; Keyvork, Chantal (EAAE Annual Conference Proceedings, 2025)
“Imagine there ́s no heaven It's easy if you try No hell below us above us, only sky [...] Imagine all the people Living life in peace ... “ John Lennon’s song “Imagine”, arguably one of the best pop songs of all times(1), is essentially an enumeration of absences. These absences, however, suggest new possibilities, alternative societies and systems: new utopias. UTOPIA, the OU-TOPOS, this “place that cannot be”2 is liberated from probabilities and reasonabilities – it is a place of ideas and ideals. In times of crises UTOPIAS boom, as they provide a dialectic service of comfort and empowerment: We escape reality by imagining alternative worlds and orders – this gives us comfort. At the same time, through this escape, we gain trust and confidence in the idea that a better reality is possible. This notion provides us with guidance and power for change. If LESS IS MUST – which utopias slumber in LESS? In John Lennon’s song, the paradigm of less goes beyond renunciation and deficiency. It elevates and liberates – it creates an abundance of possibilities. In the framework of the 2024 EAAE conference in Münster, we invited participants to discuss how utopias or scenarios of less can contribute to our common effort to overcome the multiple crises we face today.